Analisis penggunaan video conference dalam pembelajaran matematika online: studi kasus pada siswa kelas VII SMP swasta di Bandar Lampung - Rosari, Fransiska Intan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research aims to (1) knowing the preparation and process of online mathematics learning using video conferencing for class VII at SMP Swasta Bandar Lampung. (2) Knowing what are the factors of convenience and obstacles, as well as solutions in implementing mathematics learning using video conferencing for class VII at SMP Swasta Bandar Lampung during the covid pandemic-19. This type of research is descriptive qualitative research. The subjects in the study were 164 students at SMP Swasta Bandar Lampung. The data analysis used in this research are (1) inductive theory; and (2) data analysis by Miles and Huberman, namely data reduction, data presentation, conclusion drawing and leveraging. Based on interest in learning, activeness, learning motivation, and two-way communication through questionnaires submitted and the implementation of observations, it can be stated that before participating in learning students prepare cellphones/laptops, data packages, stationery, books and modules. Then in the learning process most of the students followed enthusiastically. Meanwhile, the teacher prepares everything that affects the design and process of using video conferencing for learning. In addition, video conferencing can still be developed and applied in online learning by creating innovative learning models.